Просвітницька діяльність Івана Багряного в період функціонування таборів для переміщених осіб у західних окупаційних зонах - Удот, Олександр; Udot, Oleksandr (My University, 2016)
У статті досліджено вплив просвітницької діяльності української інтелігенції на життя українців у таборах переміщених осіб у повоєнній Західній Німеччині та внесок Івана Багряного в розвиток українського громадсько-політичного життя в еміґрації. Іван Багряний розумів усю важливість підтримки й розвитку культурного життя в еміграції та саме його просвітницька діяльність стала важливим складником культурно-просвітницього життя переміщених осіб у західних окупаційних зонах.. The paper examines the impact of the Ukrainian intelligentsia educational activities on the lives of Ukrainians in the camps of displaced persons in post-war West Germany Ivana Bagryanogo that contribute to the development of Ukrainian social and political life in exile. The era of the displaced - so no coincidence, historians called 1940. The Second World War gave rise to large-scale migration. After the Second World Won several million Ukrainians who were on the territory of the former Third Reich, allies of the anti-Hitler coalition were herded into special camps.
Educational Activities Ivan Bagryany During the Operation of the Camp for Displaced Persons in the Western Occupation Zones
Keywords: репатріація; переміщені особи; табори для переміщених осіб; Іван Багряний; repatriation; displaced persons; camps for displaced persons; Ivan Bagryany; emigration; allies; Western occupation zones